Sams teach yourself Microsoft Excel 2000 programming in 21 days - Harris, Matthew (New Delhi : Techmedia, 2002)
Sams Teach Yourself Microsoft Excel 2000 Programming in 21 Days gives you the skills you need to get up and running efficiently. With this complete tutorial, you'll master the basics and move on to the more advanced features and concepts. Learn to add new functions and capabilities to your Excel files and applications. Explore built-in functions, arrays, subroutines, error handling, string operators and expressions, variables, and constants$1 (Ball in detail. Step-by-step lessons show you how to use Visual Basic to control different applications from withing Excel, and more.s
Includes index.
Keywords: Microsoft Excel (Computer file).; Electronic spreadsheets; Business -- Computer programs